2016
DOI: 10.1007/s11430-015-5260-x
|View full text |Cite
|
Sign up to set email alerts
|

Hydration effects on crystal structures and equations of state for silicate minerals in the subducting slabs and mantle transition zone

Abstract: There are potentially huge amounts of water stored in Earth's mantle, and the water solubilities in the silicate minerals range from tens to thousands of part per minion (ppm, part per million). Exploring water in the mantle has attracted much attention from the societies of mineralogy and geophysics in recent years. In the subducting slab, serpentine breaks down at high temperature, generating a series of dense hydrous magnesium silicate (DHMS) phases, such as phase A, chondrodite, clinohumite, etc. These pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 111 publications
1
1
0
Order By: Relevance
“…En 70 Fs 30 , En 44 Fs 56 , and Fs 100 have comparable values on (∂K T /∂ T ) P (−0.024(3) -−0.032(10) GPa/K) and α T (α 0 = 3.5(6)-4.1(5) ×10 −5 K −1 ). In addition, the thermal expansion coefficients of En 70 Fs 30 , En 44 Fs 56 , and Fs 100 are larger than those of anhydrous orthopyroxenes ( Figure S10; Sarver & Hummel, 1962; 10.1029/2020GL087363 Skinner, 1966;Frisillo & Barsch, 1972;Dietrich & Arndt, 1982;Jackson et al, 2003), which indicates that the incorporation of water enhances the thermal expansion of orthopyroxene, being consistent with previous studies of En 100 and other nominally anhydrous silicates (Fan et al, 2017;Xu et al, 2018;Ye, 2016). The thermal EoS parameters of the βand γ -opx phases were not successfully obtained due to the narrow data coverage (Figure 3).…”
Section: Eos Of the En-fs Orthopyroxenesupporting
confidence: 90%
See 1 more Smart Citation
“…En 70 Fs 30 , En 44 Fs 56 , and Fs 100 have comparable values on (∂K T /∂ T ) P (−0.024(3) -−0.032(10) GPa/K) and α T (α 0 = 3.5(6)-4.1(5) ×10 −5 K −1 ). In addition, the thermal expansion coefficients of En 70 Fs 30 , En 44 Fs 56 , and Fs 100 are larger than those of anhydrous orthopyroxenes ( Figure S10; Sarver & Hummel, 1962; 10.1029/2020GL087363 Skinner, 1966;Frisillo & Barsch, 1972;Dietrich & Arndt, 1982;Jackson et al, 2003), which indicates that the incorporation of water enhances the thermal expansion of orthopyroxene, being consistent with previous studies of En 100 and other nominally anhydrous silicates (Fan et al, 2017;Xu et al, 2018;Ye, 2016). The thermal EoS parameters of the βand γ -opx phases were not successfully obtained due to the narrow data coverage (Figure 3).…”
Section: Eos Of the En-fs Orthopyroxenesupporting
confidence: 90%
“…The ambient SCXRD results firmly confirmed that En 70 Fs 30 , En 55 Fs 45 , En 44 Fs 56 , and Fs 100 were successfully synthesized. However, the incorporation of several hundred ppm water results in a weak positive volume in the mixing properties of En‐Fs solid solutions (Text S2 and Figure S7; Domeneghetti & Steffen, 1992; Hugh‐Jones et al, 1997; Tarantino et al, 2002; Ohi & Miyake, 2016; Ye, 2016; Xu et al, 2018). Analyses of the high‐pressure and room‐temperature SCXRD data of En 70 Fs 30 , En 55 Fs 45 , En 44 Fs 56 , and Fs 100 indicated that all orthopyroxenes exhibited similar behaviors of phase transition, which resembled the phase transition path of En 18 Fs 82 from a previous study (Dera, Finkelstein, et al, 2013), although they contained several hundred ppm water.…”
Section: Resultsmentioning
confidence: 99%